Physiological and psychological aspects of swimmers in different training periods - Simola, R.; Samulski, D. M.; Prado, L. S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Even though many investigations have studied the psychological and physiological responses of athletes to periods of intensified training, only sparse information is provided regarding the interactions of these responses during the recovery period (Steinacker et al. 2000). Therefore, we aimed to investigate the effects of different training loads on stress and recovery perception (SRP) and on plasma activity of creatine kinase (CK). Methods: Subjects were highly trained, male swimmers (17.7 + 1.3 y.o.). SRP and CK were evaluated after two distinct training phases. On the first, subjects swam approximately 50.000 meters in the week during 5 weeks. On the second, swimmers covered an average of 25.000 meters in the week, for 2 weeks. 05 ml blood were obtained from the antecubital vein for determination of CK. SRP was evaluated using the questionnaire RESTQ-Sport for the Portuguese language (Costa & Samulski, 2005). The Student`s t-test and Pearson`s product moment correlation were used for statistical analysis. Significance level was p<0.05. Results: After the second training phase, a significant reduction of CK was observed when compared to the first measurement (261.66 + 120.04 U/L; 167.92 + 57.14 U/L), along to a reduction of scale scores in RESTQ-Sport Conflicts/Pressure (2.42 + 0.79; 1.98 + 0.9), Fatigue (2.28 + 1.07; 1.12 + 0.71), Lack of Energy (2.02 + 0.83; 1.5 + 0.61), Perturbations on Intervals (2.00 + 0.69; 1.23 + 0.75) e Lesions (2.5 + 0.91; 1,57 + 1,04). Furthermore, significant increases were seen on scales Physical Recovery (3.07 + 1.23; 3.75 + 1.08) and Being in Shape (3.23 + 1.23; 4.00 + 1.12). However, no significant correlations between scores and CK were observed in any of the sampling phases. Conclusion: Sharp training volume decreases after a period of high training loads may cause improvements on psychological and physiological profiles of the athletes investigated. However, these aspects may not necessarily be correlated. STEINACKER, J. M.; LORMES, W.; KELLMANN, M.; LIU, Y.; REIBNECKER, S.; OPTIZGRESS, A.; BALLER, B.; GUNTHER, K.; PETERSEN, K.G.; KALLUS, K.W.; LEHMANN, M.; ALTENBURG, D. Training of junior rowers before World Championships: effects on performance, mood state and selected hormonal and metabolic responses. Journal of Sports Medicine and Physical Fitness, 40, p. 327-35, 2000. COSTA, L. O. C.; SAMUSLKI, D. M. Processo de validação do questionário de estresse e recuperação para atletas (RESTQ-Sport) na língua portuguesa. Revista Brasileira de Ciência e Movimento, 13, p. 79-86, 2005.